Answer:
[tex]h^-^1(x)=0.5x+1.5[/tex]
Step-by-step explanation:
Finding the inverse of a function is similar to solving for the complete opposite of a function. An easy trick to do so is the think of the resulting value (h(x)) as another variable. Solve the equation for (x) in terms of (h(x)). Finally, switch the variable and evalutator so that one has the funciton in inverse function notation.
[tex]h(x) = 2x - \frac{4}{3}[/tex]
Inverse operations,
[tex]h(x)=2x-\frac{4}{3}\\\\h(x)+\frac{4}{3}=2x\\\\\frac{h(x)+\frac{3}{4}}{2}=x[/tex]
Simplify,
[tex]0.5(h(x))+1.5=x[/tex]
Write in inverse function notation,
[tex]h^-^1(x)=0.5x+1.5[/tex]